Hearing water temperature: Characterizing the development of nuanced perception of sound sources. Issue 3 (23rd September 2022) - Agrawal, Tanushree; Schachner, Adena
Abstract: Without conscious thought, listeners link events in the world to sounds they hear. We study one surprising example: Adults can judge the temperature of water simply from hearing it being poured. We test the development of the ability to hear water temperature, with the goal of informing developmental theories regarding the origins and cognitive bases of nuanced sound source judgments. We first confirmed that adults accurately distinguished the sounds of hot and cold water (pre‐registered Experiments. 1, 2; total N = 384), even though many were unaware or uncertain of this ability. By contrast, children showed protracted development of this skill over the course of middle childhood (Experiments. 2, 3; total N = 178). In spite of accurately identifying other sounds and hot/cold images, older children (7–11 years) but not younger children (3–6 years) reliably distinguished the sounds of hot and cold water. Accuracy increased with age; 11‐year old's performance was similar to adults. Adults also showed individual differences in accuracy that were predicted by their amount of prior relevant experience (Experiment 1). Experience may similarly play a role in children's performance; differences in auditory sensitivity and multimodal integration may also contribute to young children's failures. The ability to hear water temperature develops slowly over childhood, such that nuanced auditory information that is easily and quickly accessible to adults is not available to guide young children's behavior. Highlights: Adults can make nuanced judgments from sound, including accurately judging the temperature of water from the sound of it being poured. Children showed protracted development of this skill over the course of middle childhood, such that 7–11‐year‐olds reliably succeeded while 3–6‐year‐olds performed at chance. Developmental changes may be due to experience (adults with greater relevant experience showed higher accuracy) and the development of multimodal integration and auditory sensitivity. Young children may not detect subtle auditory information that adults easily perceive. Abstract : Adults can make nuanced judgments from sound, including accurately judging the temperature of water simply from the sound of it being poured. Children showed protracted development of this skill over the course of middle childhood, such that 7–11 year‐olds reliably succeeded at hearing water temperature, while 3–6 year‐olds performed at chance. Developmental changes may be due to experience (adults with greater relevant experience showed higher accuracy) as well as the development of multimodal integration abilities and auditory sensitivity.